On the Nash equilibrium in the inspector problem - Sabaliauskas, Martynas; Mockus, Jonas (Lietuvos matematikos rinkinys, 2014)
Inspector problem represents an economic duel of inspector and law violator and is formulated as a bimatrix game. In general, bimatrix game is NP-complete problem. The inspector problem is a special case where the equilibrium can be found in polynomial time. In this paper, a generalized version of the Inspector Problem is described with the aim to represent broader family of applied problems, including the optimization of security systems. The explicit solution is provided and the Modified Strategy Elimination algorithm is introduced.
Keywords: game theory; Nash equilibrium; polynomial complexity